Predictors of Normalization of Circulating Interleukin-6 after Cardiac Myxoma Resection - Yuan,Shi-Min (2019)
Abstract Objective: To disclose the relationships between the anatomic features of cardiac myxomas and plasma interleukin (IL)-6 levels. Methods: Twelve patients undergoing cardiac myxoma resection at The First Hospital of Putian, Teaching Hospital, Fujian Medical University were enrolled into this study. Pre- and postoperative IL-6 levels were determined by an enzyme-linked immunosorbent assay method, and correlations between cardiac myxoma dimension or volume and plasma IL-6 levels were analyzed. C-reactive protein (CRP) levels were also evaluated. Results: IL-6 and CRP levels were significantly decreased one month after cardiac myxoma resection in comparison to preoperative values. IL-6 and CRP levels did not differ between patients with a cardiac myxoma of irregular appearance and those with a myxoma of regular gross appearance, or between patients with a pedicled or a sessile myxoma. Decrement of IL-6 of patients with irregular cardiac myxomas was much higher than that of patients with regular ones, while no intergroup difference was noted in decrement of CRP. A close direct correlation was noted between IL-6 levels and maximal dimension (length) or volume of cardiac myxomas, whereas CRP levels only correlated with maximal dimension of cardiac myxomas. Conclusion: Anatomic features of cardiac myxomas (sessile, irregular appearance, maximal dimension, and volume) could be determinants of the patients' circulating IL-6 levels. IL-6 was likely to be a more sensitive biomarker than CRP in predicting the inflammatory status of patients with cardiac myxoma. Sessile and irregular cardiac myxomas might predict more severe inflammatory conditions for their more abundant endothelial cells and IL-6 overproduction.